EFEKTIVITAS PENGGUNAAN APLIKASI NEARPOD DALAM PEMBELAJARAN IPA MATERI BAGIAN-BAGIAN TUMBUHAN PADA KELAS IV-A DI SDN BULAK RUKEM I/258 SURABAYA - Fefi Utami; Ninik Zahrotur Rohmaniyah; Laily Mar'atul Maghfiroh; Tri Puspita Agustina; Hanifah Muslimah; Ika Dian Rahmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This This research was conducted at Elementary School Bulak Rukem I/258 Surabaya. The study examines the effectiveness of using the Nearpod application as a learning tool for the topic of plant parts in class IV-A, the improvement in pre-test and post-test results, and student responses. During the research, data was collected through pre-tests, post-tests, questionnaires, and documentation. The methods used were quantitative, including N-Gain tests, normality tests, and non-parametric Wilcoxon tests. Based on the data analysis, it was found that the Nearpod application is effective for teaching the topic of plant parts in science, as shown by the N-Gain test results of 0.3 ≤ 0.6866 ≤ 0.7. Subsequently, a normality test revealed that the data produced was not normal, indicated by the significance values of both the pre-test and post-test being < 0.05. Then, a non-parametric Wilcoxon test was conducted, yielding an Asymp. Sig (2-tailed) value < 0.05 (0.000 < 0.05), indicating a significant difference in the data. The questionnaire results showed that 85% of students responded positively to the Nearpod application for the Science topic of plant parts.